Educational transformation through ethno-STEM: Exploring its potential, challenges, and impact on 21st century skills - Agustinus, Subagja; Permana, Irvan; Ardianto, Didit; Permanasari, Anna; Nuraeni, Eni (Assimilation: Indonesian Journal of Biology Education, 2025)
This study aims to analyze Ethno-STEM-based learning, focusing on the implementation, challenges, and its impact on students' critical and creative thinking skills. The study employs a qualitative analysis method using an open coding approach on nine relevant articles published between 2020 and 2024. The analysis results indicate that integrating Ethno-STEM with a Project-Based Learning (PjBL) approach is effective in enhancing students' critical and creative thinking skills, with most research findings showing significant improvements in both skills. The main challenges identified include educators' limited understanding of Ethno-STEM, technological constraints, and difficulties in integrating local culture into the STEM curriculum. Several studies also highlight the need for teacher training and infrastructure development to support the sustainable implementation of Ethno-STEM. Overall, Ethno-STEM-based learning significantly contributes to the development of 21st-century skills, particularly in enhancing students' creativity, critical thinking, and cultural awareness. These findings recommend further development of Ethno-STEM-based learning resources, such as e-modules and learning syntax, to support educational practices oriented toward local cultural sustainability. This study provides a critical foundation for more inclusive and value-based curriculum innovations in the future.